Average Distance of Certain Graphs - Jasintha Quadras; K. Arputha Christy; A. Nelson; S. Sarah Surya (International Journal of Mathematics And its Applications, 2017)
Mean distance or average distance is used in studying the efficiency of networks or more generally `good networks' which are often characterized by small distance. It is also used as a tool in analytic networks where the performance time is proportional to the distance between any two nodes. In this paper, we compute the Wiener index and the average distance of generalised prisms, uniform $n$-wheel split graph, uniform $n$-star split graph and cyclic split graph.